Understanding the Development of Alphabet Knowledge in At-Risk Populations: The Influence of Pre-Literacy Skills - (:unkn) unknown (My University, 2012)
In the current research, alphabet knowledge has been confirmed as a critical component of children's developing emergent literacy proficiency. The assessment of pre-literacy skills, such as alphabet knowledge, plays an important role in the management of children at-risk for poor reading outcomes. This study aimed to better understand the influence of phonological awareness skills, print skills, and receptive vocabulary on the development of alphabet knowledge in at-risk preschool-age children. Statistical analyses revealed that a significant unique relationship was present between phonological awareness skills and the development of alphabet knowledge. Furthermore, this study identified three clusters of children based on the amount of growth in their alphabet knowledge. Final analyses were completed within the identified clusters to determine the specific types of letters learned by each cluster. These analyses revealed that the clusters of children learned different types of letters based on the amount of growth in their alphabet knowledge. These findings equip practitioners with the additional evidence base necessary to be confident in using measures of alphabet knowledge and phonological awareness to identify children at-risk for later reading difficulties. The results of this study confirm that alphabet knowledge can be used as a curriculum-based measure, as well as a general outcome measure. These results are also significant in helping teachers selecting appropriate curriculum materials for teaching alphabet knowledge in pre-school and kindergarten classrooms.
Keywords: African American; Alphabet Knowledge; Curriculum Development; Emergent Literacy; General Outcome Measure